THE IMPLEMENTATION OF MULTIMEDIA IN THE TEACHING AND LEARNING PROCESS OF ENGLISH AT SMPN 14 BANJARMASIN - Budi Utami, Dian (Journal Compound: Improving the Quality of English Education, 2021)
This research was aimed to explain the implementation of computer and LCD as multimedia and the response of the students on the implementation of computer and LCD as multimedia in the teaching and learning process of English at SMP Negeri 14 Banjarmasin school year 2015/2016. This research was a descriptive case study with a qualitative research design. The subjects of the research are two English teachers who were teaching in the seventh grade, the principal, and the students of the seventh grades from seven classes in similar level. The findings revealed that the implementation of multimedia in SMP Negeri 14 Banjarmasin was about 3 years. This school had Multimedia Room so the English teachers and students can use it based on the schedule prepared. Therefore, the implementation of multimedia as a tool to help the teacher and students in reaching the goals of learning followed some steps such as: Preparation, Implementation, and Follow-up. In implementing computer and LCD as multimedia, the English teachers used Media Player Classic, Power Point, and Internet in Multimedia Room. So, the implementation of computer and LCD as multimedia made the teaching and learning process was easy for all, not just for the teacher but also for students because computer and LCD was one of several things that truly support the teaching and learning process.